Insight into the syntheses, performances and mechanisms of organically modified adsorbents for mercury ion sensing and removal. Issue 5 (October 2021) - Tanimu, Abdulkadir; Alhooshani, Khalid
Abstract: Organically modified materials constitute adsorbent materials that are made of organic functional groups grafted on organic substrate or inorganic substrate. The organically modified materials are the most widely used adsorbents for Hg(II) removal. This is because of the abundant organic and inorganic substrates that have desirable properties and ease of surface chemical modifications. These modifications are generally carried out on the substrates framework and their functional groups. In-depth understanding of the chemical reactions that are involved in the substrates synthesis and modifications, and how these relate to the Hg(II) adsorption mechanism will guide future research in the design and development of advanced adsorbents. In this review, the most recent advances in the synthesis of organically modified Hg(II) adsorbents, and how their properties relate to the Hg(II) adsorption mechanism have been presented and summarized. Novel emerging adsorbents such as the calixarene-based, covalent organic frameworks, supramolecular polymers and metal organic frameworks, and how luminescence sensing ability is utilized in some of these adsorbents for trace level detection of Hg(II) have been highlighted. Graphical Abstract: ga1 Highlights: Review on organically modified adsorbents for Hg(II) removal is presented. Adsorbents structure-adsorption mechanism nexus were interpreted. COFs luminescence property allows tandem detection and removal of Hg(II). Supramolecular polymers' abundant binding sites translates to high adsorption capacity. MOFs functionalization and the challenges therein have been explained.